Clinical Features of COVID-19 Patients in Thi-Qar Province - A Abd, Akram; Salman Mahdi, Dawood; Edan Alsaimary , Ihsan (University of Thi-Qar Journal of Science, 2023)
Coronavirus disease–2019 (COVID-19) was detected in Wuhan, China, in December 2019, resulting in a 2% fatality rate. Severe Acute Respiratory Syndrome   Coronavirus 2 (SARS-CoV-2) is the virus that causes this illness, and it is a newly discovered zoonotic strain.TLRs, which identify microbial components originating from invading pathogens, are implicated in the activation of innateresponses to SARS-CoV-2 infection as well as the hyperinflammatory phenotype of COVID-19.Aim: Determining the most common clinical factors in people with Covid and adopting them as the initial clinical diagnosis. Toreduce the risk of disease.Results: The highest age group of patients with covid_19 was (45-54 years) were 26 (29.5%) of all study patients. The mostfrequent symptom was fever (82.9%), and the least was diarrhea (21.6%). The study found no significant positive effect onsmoking and non-smokers.